IMPLEMENTASI LATIHAN CIRCUIT TRAINING MODIFIED TERHADAP PENINGKATAN VO2MAX PESERTA EKSTRAKURIKULER BOLA VOLI SMP NEGERI 1 KRAMATMULYA - SHELLA AWALIA INSANI DEWI (STKIP Muhammadiyah Kuningan, 2021)
This study aims to increase VO2Max in volleyball extracurricular participants at SMPN 1 Kramatmulya through the Modified Circuit Training method. This research is an experimental study which was carried out for approximately two months, with the intensity of meeting three times a week. In total there are 6 weeks with the frequency of training 3 times in 1 week. In April - May 2021. Data were collected through pretest and posttest. The data were analyzed using SPSS version 23. The results showed that the modified circuit training method was very suitable to be applied to male volleyball extracurricular participants at SMPN 1 Kramatmulya. Because with the modified circuit training program, extracurricular participants can increase their aerobic endurance (VO2Max). The conclusion is that modified circuit training can increase the VO2Max of volleyball extracurricular participants